2019
DOI: 10.3168/jds.2018-15715
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for raw sheep milk storage in smallholdings: Effect of freezing or long-term refrigerated storage on microbial growth

Abstract: We assessed the effects of freezing and refrigeration over long periods on the microbiological quality of sheep milk. The raw milk was frozen in 1-L plastic bags or 5-L milk buckets and, after 1 mo, thawed at 7 or 25°C. We evaluated these samples immediately after thawing (d 0) and after 1 d of storage at 7°C. Furthermore, we stored fresh raw milk at 7°C for 10 d in the same packages and in a bulk milk cooler at 4°C (adding 10% of fresh raw milk daily). The total bacterial, total psychrotolerant, and proteolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 27 publications
(42 reference statements)
1
20
0
Order By: Relevance
“…However, significant changes were only observed after 7 and 9 days of storage, respectively, with acidity values from 0.22 to 0.27 g/100 ml and pH from 6.45 to 6.22 (Figure 1). Other authors also reported similar results for nonbovine milk (De La Vara et al, 2018; Tribst, Falcade, & De Oliveira, 2019), which reinforces that pH cannot be used as an indirect parameter to control the quality of sheep milk due to its high‐buffering capacity. Moreover, titratable acidity should be used with caution due to the natural variation of acidity in sheep milk (Tribst, Falcade, Leite Júnior, et al, 2019), leading to high standard deviation and, consequently, requiring a great change to be significant.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…However, significant changes were only observed after 7 and 9 days of storage, respectively, with acidity values from 0.22 to 0.27 g/100 ml and pH from 6.45 to 6.22 (Figure 1). Other authors also reported similar results for nonbovine milk (De La Vara et al, 2018; Tribst, Falcade, & De Oliveira, 2019), which reinforces that pH cannot be used as an indirect parameter to control the quality of sheep milk due to its high‐buffering capacity. Moreover, titratable acidity should be used with caution due to the natural variation of acidity in sheep milk (Tribst, Falcade, Leite Júnior, et al, 2019), leading to high standard deviation and, consequently, requiring a great change to be significant.…”
Section: Resultsmentioning
confidence: 54%
“…The refrigerated samples were also monitored daily for 9 days for pH, acidity, total aerobic bacteria counts (TBC), and total psychrotrophic bacteria counts (TPC) (Downes & Ito, 2001) in duplicate. The modified Gompertz model (Equation 1) was adjusted to the results (Tribst, Falcade, & De Oliveira, 2019) to describe the bacterial growth curves of refrigerated sheep milk.lnCC0goodbreak=Aexp}{goodbreak−exp][2.781.μmaxA.)(λgoodbreak−tgoodbreak+1,where C is the microbial population (CFU/ml) at time t (days); C 0 is the initial microbial population (CFU/ml); A is the asymptote (ln C max / C 0 ), representing microbial amplitude; μ max is the maximum specific growth rate during the exponential growth phase, and λ is the lag time (days). The three parameters ( A , μ max , λ ) were calculated by nonlinear regression using CurveExpert® Basic 2.0 (Hyams Development, USA).…”
Section: Methodsmentioning
confidence: 99%
“…These results could be explained by the greater immunological activity of sheep milk, which restricts bacterial proliferation during the first hour after milking (Ramos and Juarez ). Results observed by Tribst et al () also showed a long period of time (up to 10 days) for sheep milk to reach unacceptable bacterial counts under refrigeration. Necidová et al () demonstrated that Bacillus cereus growth was slower in sheep milk at 22 °C when compared with cow and goat milk, but it was not possible to establish whether this difference was related to intrinsic characteristics of sheep milk or different bacterial counts and types between the studied sources of milk.…”
Section: Resultsmentioning
confidence: 80%
“…The longer the phase change time, the slower the formation of ice crystals, which increased migration of calcium out of the micelles, as well as the concentration of soluble calcium [ 46 ]. Thermal histories of the sheep’s milk freezing process in different packages, including 5 L packages, have been presented by Tribst et al [ 47 ].…”
Section: Resultsmentioning
confidence: 99%